Reward signals in the motor cortex: from biology to neurotechnology - Gerard Derosiere; Solaiman Shokur; Pierre Vassiliadis (Nature Communications)
Abstract Over the past decade, research has shown that the primary motor cortex (M1), the brain’s main output for movement, also responds to rewards. These reward signals may shape motor output in its final stages, influencing movement invigoration and motor learning. In this Perspective, we highlight the functional roles of M1 reward signals and propose how they could guide advances in neurotechnologies for movement restoration, specifically brain-computer interfaces and non-invasive brain stimulation. Understanding M1 reward signals may open new avenues for enhancing motor control and rehabilitation.